Servant Leadership in Public Health Services: Examining Influential Factors and Key Drivers - Ferry Fadzlul Rahman; Herni Johan; Siti Noorbaya; Abdullah Mubaroq; . Surahman (Journal of Iranian Medical Council, 2026)
Background: This study examines the relationships between servant leadership and its influence on burnout prevention, employee empowerment, happiness, eudaimonic well-being, and motivation to retain employment among public health service staff. Methods: A cross-sectional survey was conducted from March to June 2024 at the Samarinda City Public Health Office, Indonesia. A total of 188 were selected via stratified random sampling. Data were collected using a validated Likert-scale questionnaire covering five constructs. Spearman’s rank correlation was applied to assess the strength of bivariate associations between servant leadership and each construct, while multiple regression was used to evaluate their unique and combined contributions after controlling for overlap. Results: Correlation analysis showed that all five predictors were positively associated with servant leadership. Spearman’s rho values were 0.381 for burnout prevention, 0.562 for empowerment, 0.642 for happiness, 0.442 for eudaimonic well-being, and 0.296 for motivation to retain employment (all p